The directions of the Diploma in Information Management part 6 students of UiTM Kedah after the graduation / Siti Suriyani Muhamad - Muhamad, Siti Suriyani (Faculty of Information Management, 2010)
Making the transition from the tertiary study to the workforce is a journey undertaken by thousands of graduates each year. Therefore, a study of the direction of the students after the graduation among the Diploma in Information Management Part 6 students, UiTM Kedah was conducted. The respondents for this research are undergraduate’s students which will graduates soon among Diploma in Information Management Part 6 students, UiTM Kedah. The objective of this study is to study the relationship between the directions of the students after graduate whether being employed, further the study, getting married or remain unemployed with the factor influence such as money, family and student’s attitudes and behavior. In this study, there are independent variables which are the directions of the students after graduate and dependent variables which are money, family and student’s attitudes and behavior.